2015
DOI: 10.1186/s13633-015-0017-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual development and quality of life outcomes in females with congenital adrenal hyperplasia

Abstract: Background/AimsOutcome information regarding females with classical congenital adrenal hyperplasia (CAH) have generally suggested poor quality of life (QoL), general maladjustment, problems regarding sexuality, and decreased fertility. The aim of this study was to assess QoL, psychosocial adaptation, and psychosexual characteristics, includingchildhood gender role behavior, gender identity, and sexual orientation in females with CAH.MethodsFemale patients with 21-hydroxylase deficiency CAH were evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
2
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
0
25
2
5
Order By: Relevance
“…Many patients experience poor intimate relationships due to the fear of rejection, stigmatization, and bullying (Cohen‐Kettenis, ). The difficulty in sexual intercourse was due to physical or psychological barriers (Cohen‐Kettenis, ; Kanhere et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Many patients experience poor intimate relationships due to the fear of rejection, stigmatization, and bullying (Cohen‐Kettenis, ). The difficulty in sexual intercourse was due to physical or psychological barriers (Cohen‐Kettenis, ; Kanhere et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For adults, the outcome results are mixed. Some reports show unaffected psychological adjustment measured by self-assessment instruments, (158,159) other report impaired QoL and wellbeing (133) for patients with CAH. Health related QoL outcome domains that are most often affected is general health and vitality (160).…”
Section: Cahmentioning
confidence: 99%
“…The lowered satisfaction was mostly attributed to low breast volume. In one study, women with CAH expressed complaints about lack of breast development (Kulshreshtha et al, 2012), albeit in a sample with significant delay of adequate treatment, and in another study 35% of women reported they wanted larger breasts (which was more frequently reported than dissatisfaction with genital appearance; 26%) (Kanhere et al, 2015). One-third of the women surveyed with CAH and 46,XY karyotype reported breast dissatisfaction, which was more prevalent than in the matched controlled sample (Ediati et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to breast satisfaction, even fewer studies have been published (Migeon et al, 2002;Bannink et al, 2006;Bartolin et al, 2012;Kulshreshtha et al, 2012;Ediati et al, 2015;Kanhere et al, 2015;van de Grift et al, 2018). In both males and females with DSD, breast satisfaction has been observed to be lower than control values (Ediati et al, 2015).…”
Section: Introductionmentioning
confidence: 99%